Biomarkers in retinopathy of prematurity: a systematic review and meta-analysis - Almutairi, Mariam; Chechalk, Katherine; Deane, Emelia; Fox, Rebecca; Janes, Ava; Maguire-Henry, Tidgh; McCabe, Devin; O'Connor, Cole; Quirk, Joseph; Swan, Evan; White, Katherine; McCreery, Kathryn; et al. (Frontiers in Pediatrics, 2024)
Aim Retinopathy of prematurity is a significant global cause of childhood blindness. This study aims to identify serum biomarkers that are associated with the development of ROP. Methods A systematic review and meta-analysis was conducted using PRISMA guidelines. Three databases were searched (Pubmed, Scopus and Web of Science) from 2003 to March 2023. Only studies investigating serum biomarker levels in preterm infants (<37 weeks gestation) were included. Results Meta-analysis suggests that low serum IGF-1 levels have a strong association with the development of ROP [SMD (95% CI) of −.46 [−.63, −.30], p < .001]. Meta-analysis suggests that higher serum glucose levels were associated with the development of ROP [SMD (95% CI) of 1.25 [.94, 1.55], p < .001]. Meta-analysis suggests that thrombocytopenia is associated with the development of ROP [SMD (95% CI) of −.62 [−.86, −.37], p < .001]. Conclusion Low levels of serum IGF-1, high levels of serum glucose and thrombocytopenia all appear to have the strongest association with the development of ROP out of the 63 biomarkers investigated in this review. These associations highlight their potential use as diagnostic biomarkers in ROP, though further research is needed to establish the exact relationship between these biomarkers and disease pathogenesis.